Peran Glass Ceiling dan Work Engagement Dalam Profesi Dosen di Era Digital (Studi Kasus Dosen Wanita di Perguruan Tinggi Kabupaten Grobogan) - Fariha Azzahra; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background: The glass ceiling phenomenon has become a crucial concern for female employees, especially for companies where a glass ceiling has appeared, causing lower opportunities for female employees to go to the top level, even though from a competency and skills perspective, women are not much different from men. Many previous studies have been carried out in profit companies, so this study aims to analyze the role of the glass ceiling that appears among female employees in non-profit institutions, namely universities in Grobogan Regency. The formulation of the problem is what is the role of the glass ceiling in supporting the career advancement of female lecturers at Grobogan district tertiary institutions. Purpose: In solving the problem formulation can be done with the specific objectives of this research are 1) to analyze the influence of family factors on the role of the glass ceiling, 2) To analyze individual influence factors on the role of the glass ceiling, 3) To analyze the organizational influence factors on the role of the glass ceiling, 4) To analyze the cultural influence factors on the role of the glass ceiling, 5) To analyze the effect of the role of the glass ceiling on work engagement. Methods: The population in this study were all female lecturers at Grobogan District Higher Education with a sample of 54 lecturers women to be used as research samples. Data collection tool with a questionnaire which was analyzed using SEM with program SmartPLS. Conclusion: The results showed that the family factor influence on the role of the glass ceiling, Individual factors have a positive effect significant effect on the role of the glass ceiling, Organizational factor has no effect on the role of the glass ceiling, Cultural factor a significant positive effect on the role of the glass ceiling and Glass ceiling has a significant positive effect on work engagement. Suggestion: Job promotion is also based on a review based on the qualifications, skills, competencies and work experience of employees by the selection team at the company. As for further research, it is recommended to conduct further research in sectors other than education, add several variables related to women's career advancement and conduct qualitative data collection related to the issue of the glass ceiling phenomenon.